Experimental Acanthamoeba keratitis: I. Preliminary findings. Issue 9 (September 1990) - Larkin, D F; Easty, D L
Abstract : Experimental Acanthamoeba keratitis was induced in Wistar rats by intrastromal inoculation of Acanthamoeba polyphaga cysts. Keratitis developed in all corneas injected and was characterised by a diffuse granular opacity. The animals were examined for 70 days and a gradual reduction of keratitis was observed. Pathological sections showed liquefactive stromal necrosis and Acanthamoeba localised in deep stroma persisting to 70 days. A brisk inflammatory infiltrate of neutrophils and macrophages was seen in the early days of infection. Severity of keratitis was found to correlate with inflammatory activity in pathological sections. The uses of an animal model of Acanthamoeba keratitis are described.